Oral Cancer's New Enemy: Goniothalamus umbrosus Targets Oral Squamous Cell Carcinoma and Spare Human Gingival Fibroblast Cells - Aziz, Nuraini Che; Alahmad, Basma Ezzat Mustafa; Kashmoola, Muhanad Ali; Lestari, Widya; Rosdy, Nik Mohd Mazuan Nik Mohd; Mokhtar, Khairani Idah (European Journal of Dentistry, 2025)
Objective Oral squamous cell carcinoma (OSCC) is the prevailing type of oral cancer, representing poor prognosis and elevated mortality rates. Major risk factors for OSCC include the use of tobacco products, alcohol consumption, betel quid chewing, and genetic mutation. Goniothalamus umbrosus is traditionally consumed by cancer patients to fight against tumor growth. To date, research on the anticancer potential of G. umbrosus in oral cancer remains deficient. This study aimed to evaluate the anticancer potential of G. umbrosus in OSCC cell lines (SCC-15 and HSC-3) and compare its cytotoxic activity on human gingival fibroblast (HGF) cell lines.Material and Methods Leaves of G. umbrosus were cleaned, air dried, ground, and soaked for 24 hours with methanol and hexane repeatedly three times, respectively. Pooled extracts of each solvent were then dried with a rotary evaporator. Anticancer potential of G. umbrosus extracts was evaluated on two OSCC cell lines (SCC-15 and HSC-3) and a normal HGF cell line incubated for 24, 48, and 72 hours by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The cytotoxicity of cisplatin was assessed as a positive control. Morphological changes of cells were observed under an inverted microscope.Results MTT assay revealed that G. umbrosus methanol extract (GUME) displayed moderate anticancer activity on SCC-15, HSC-3, and HGF cell lines with IC50 values of 126.67, 90.5, and 87.33 µg/mL following 72 hours' incubation times, respectively. G. umbrosus hexane extract (GUHE) exerted moderate anticancer activity against SCC-15 and HSC-3 cell lines with IC50 values of 171 and 174 µg/mL, respectively, but weak cytotoxicity against the HGF cell line with IC50 value of 343.5 µg/mL. Cisplatin exerted a strong cytotoxic impact on both OSCC and HGF cell lines. Morphological observation revealed the characteristics of cells undergoing apoptosis.Conclusion The findings show that GUHE was more selective in inhibiting the proliferation of oral cancer cells than GUME by exerting moderate cytotoxicity on OSCC cell lines and weak cytotoxicity in HGF cells, while GUME exerted moderate cytotoxicity on both. These findings suggest a more targeted anticancer effect by GUHE as compared with cisplatin, which exerted nonselective cytotoxic activity. These findings provide a groundwork for the development of more targeted plant-based treatment for oral cancer.
Keywords: Goniothalamus umbrosus; oral squamous cell carcinoma; human gingival fibroblast; selective cytotoxicity